Сезонна динаміка колориту паркових ландшафтів м. Києва - Мавко, Мар’яна Степанівна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». Національний університет біоресурсів і природокористування України. Київ, 2018. У дисертації узагальнено теоретичні, методичні та практичні положення щодо оцінювання і формування колориту паркових ландшафтів, уточнено чинники його мінливості, проведено оцінювання колориту шести парків м. Києва різного функціонального призначення за порами року, шістьма та 11 фенологічними підсезонами. Систематизовано наявну наукову інформацію щодо колористики ландшафту. Висвітлено розроблену методику оцінювання колориту ландшафту, яка дає можливість виявити панівні кольори і їхні відсоткові співвідношення. Проаналізовано відповідність між функціональним призначенням парків та їх колоритом. Обґрунтовано поняття «колорит паркових ландшафтів» та «функціональний (цільовий) колорит» та здійснено підбір колірних гам для формування колориту парків залежного від їхніх тематичних особливостей. Розроблено науково-методичні рекомендації щодо формування колориту паркових ландшафтів
Thesis for awarding the scientific degree of candidate of agricultural sciences in speciality 06.03.01 «Forest Plantations and hytomelioration». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. In the dissertation theoretical, methodological and practical positions concerning estimation and formation of park landscapes colouring are generalized, the factors of its variability are specified, as well as the peculiarities of their influence on the colour of landscapes, estimation of colouring of 6 parks of Kyiv with different functional purposes is carried out. The available scientific information on the coloristics of the landscape, the colour characteristics of plants and their seasonal variability, and the principles of the use of colour when creating phytocomposites are systematized. The need for research aimed at studying the colour of objects of landscape architecture, within the framework of the formation of the coloristic architectural and natural environment of the city is worth noting. The complexity of studying the colour in the natural environment lies in its variability. The developed methodology for assessing the colour of the landscape is described, which gives an opportunity to evaluate both the overall colouring of the park environment and the colouring of a separate landscape and to identify the main colours that form the colour of the landscape object and their percentage ratios. The assessment of the park landscapes colouring of Kyiv parks was performed, the results of which determined a system of factors (optical and climatic) that influence the perception of colour forming components of the park landscape and predetermine the variability of its landscapes and their classification is proposed. The influence of optical factors on the park colouring is significant – the typical colour change (green colour of plants) which characterises the air perspective is revealed and its limits are set: starting from a distance of 1.5 km, the planting obtain the blue colour at a distance of 13–14 km from the viewpoint. In particular, among the climatic factors, the influence of weather conditions on the park colouring has been confirmed, in particular the patterns of changing the colour of wet and bright objects, the effect of «bleaching» colours in the fog, changing the plantings colouring depending on the time of day. It is established that the defining factors among the colour forming components and factors are the own colours of the components of the park landscape, and both optical and climatic factors act as «filters» that influence the process of perceiving the park landscape colouring by a person. The division of seasons and subseasons when one can see the changes of park colouring, is determined and specified. The correspondence between the functional purpose of the parks and their colouring was assessed and the colourring of most of the Kyiv parks is not consistent with their functional purpose due to a number of factors, in particular – the combination of contradictory functional zones, which causes difficulty in forming the general target colouring of the park, which is a significant feature for memorial parks (in particular, war themes and tragic events). The colouring of researched parks (by seasons, by 6th and 11th phenological subseaons during 2012–2014 and 2016–2017) was estimated. In the autumn, in parks, the warm yellow-green range of autumn leaves predominate, after the fall of the leaves the proportion of brown colour of branches and tree trunks grows. Unlike M. Rylsky Park in Holosiivo, where the green colour of plantings in the winter colouring is absent at all, in the Peremoha Park the proportion of green colour is 6.5 % (since the park's dendrological base is an array of Pinus sylvestris L.), in the Feofaniya Park – 5.8 %, which, in comparison with other parks, is quite high. The winter colouring varies depending on the snow or snowless aspect of nature, temperature transition below or above 0º C. The spring season is characterized by significant variability (from snowy spring to the height of spring and presummer subseason) and is rapidly changing. The awakening of spring or «bare spring» occurred in the first decade of March, a green colour appears (7.8 %) in the colouring of plantings. In the midst of the spring or the green spring, the proportion of the green colour of the plant grows substantially (up to 19.7 %). In contrast, the colour of plantings during the summer subseaons is the most stable and does not change significantly (the green colour of plantings in the beginning of summer occupies 50.6 % in the park colouring, in the sub-season the full summer is 51.0 %, in the second half of the summer – 56.5 %, at the decline of the summer is up to 52.2 %. The quantitative indexes of changes in the green colour of plantings and brown colour of branches and trunks, which shows the vegetation season, accumulation and loss of green mass of plants, are analyzed. Based on the results of assessing the park colouring, taking into account the seasonal dynamics 10 phases of changing their colouring were identified: the beginning of the autumn, golden autumn, deep autumn, snowless and snowy winter, the beginning of snowmelting (striking spring), the awakening of spring (bare spring), the height of spring (green spring), early summer and the fall of summer. Based on the carried out researches the concept of «park landscapes colouring» and «functional (target) colouring» were substantiated, and the selection of colour schemes for the formation of the parks colouring depended on their functional features and ideological load is made. Scientific and methodical recommendations for the formation of the park landscapes colouring have been developed. The principles of the selection of solid and combined colours wood plants for phytodesign usage are substantiated. In particular, the maximum distance is set for use of combined and solid colours plants in park landscapes, which is 15–20 m and 100–120 m, respectively. Combined colours plants are best perceived with insignificant viewing distance (0.5–3 m) and have an effect on the colouring of a particular view. The integrity of the colour of the plant's spot in the landscape depends on the density and structure of the crown
Keywords: колорит; сезонна динаміка; паркові ландшафти; мінливість; композиція насаджень; функціональний колорит; colouring; seasonal dynamics; park landscapes; variability